The phosphorylation of an acidic protein of the large ribosomal subunit of Krebs II ascites cells. - Leader, D P (1977)
The ribosomes of Krebs II ascites cells contain an acidic protein, apparently analogous to proteins L7/12 of Escherichia coli. When ascites cells were incubated with [32P]Pi, this protein became labelled, indicating that it is a phosphoprotein.